ANALYSIS OF FACTORS THAT INFLUENCE IMPULSE BUYING: A CASE STUDY ON E-COMMERCE USERS IN JAKARTA - Wildan Nadzimi; Prastyo Hadi (Jurnal Manajemen, 2024)
E-commerce is a place for people to make both planned and impulsive purchases, especially for younger generations such as gen Z. This study aims to determine the effect of website quality, sales promotion, and shopping lifestyle on impulse purchases in generation Z e-commerce users (Tokopedia, Shopee, Lazada) in DKI Jakarta. This study uses quantitative descriptive analysis which then the data is obtained from distributing questionnaires using non-probability sampling method with purposive sampling. The sample used was 100 generation Z people aged 17 years and over e-commerce users (Tokopedia, Shopee, Lazada) in DKI Jakarta. The data analysis used is descriptive and inferential data analysis techniques using Partial Least Square (PLS) with SmartPLS 3.2.9 software. The results of this study indicate (1) website quality has a positive and significant effect on impulse purchases with a path coefficient of 0.256. (2) sales promotion has a positive and significant effect on impulse purchases. Shopping lifestyle has a positive and significant effect on impulse purchases with a path coefficient of 0, 376.